High-strength light and thin building ceramic material and preparation method thereof

CN122916613APending Publication Date: 2026-10-16ENPING XINJINCHENG CERAMICS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611265313.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]有鉴于现有技术的上述缺陷,本发明所要解决的技术问题是针对现有再生固体废弃物制备轻薄建筑陶瓷材料时,包覆型增强颗粒的包覆层在含水浆料中的结构稳定性不足,颗粒内核、包覆层与陶瓷基体之间烧成收缩不匹配,进而导致界面孔隙和微裂纹较多,以及所得轻薄陶瓷材料断裂模数、抗冲击性能和热震稳定性不足的问题,提供一种高强度轻薄化建筑陶瓷材料及其制备方法

Benefits of technology

[0029] 1. This invention comprises a composite interface modifier consisting of boehmite nanofiber dispersion, zirconium ammonium carbonate solution, and yttrium sol, which is introduced into the base coating slurry through simultaneous addition. The hydroxyl groups on the surface of the boehmite nanofibers can provide adsorption and loading sites for zirconium and yttrium species, thereby reducing the local agglomeration of zirconium and yttrium components in the coating slurry and improving the uniformity of the distribution of the modifier in the coating layer.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of high-strength light and thin building ceramic materials and preparation method thereof, it is related to building ceramic material technical field.The method will waste concrete, waste ceramic tile and waste glass be made into particle and powder respectively, with waste ceramic particle and waste concrete particle as core, modified slurry containing composite interface modification component is coated on its surface, and coated type reinforcing particle is prepared;Again, it is mixed with ceramic matrix slurry, and is made into light and thin building ceramic material by spray granulation, stale, pressing, segmented drying and sintering.The application can reduce interface pore and microcrack, improve sintering density, fracture modulus, impact resistance and thermal shock stability, and realize the resource utilization of solid waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building ceramic materials technology, and in particular to a high-strength, lightweight building ceramic material and its preparation method. Background Technology

[0002] Architectural ceramic materials are widely used in building walls, floors, and decorative projects. As architectural ceramics develop towards larger sizes and thinner profiles, the reduced material thickness makes them more susceptible to the effects of internal pores and interfacial microcracks on flexural strength, impact resistance, and thermal shock stability. Simultaneously, the quantity of waste ceramic bricks, waste concrete, and waste glass is constantly increasing; utilizing these resources in architectural ceramic production helps reduce the consumption of natural mineral raw materials and improves the resource utilization rate of solid waste.

[0003] Existing technologies typically involve crushing or grinding the aforementioned solid wastes and then directly incorporating them into ceramic blanks. However, the composition, particle size, firing shrinkage rate, and thermal expansion properties of different waste materials vary, which can easily lead to uneven sintering of the blank, insufficient interfacial bonding, and increased porosity.

[0004] CN104326734A discloses an ultra-thin recycled ceramic brick and its manufacturing method. The method involves mixing electrolytic manganese waste residue, porcelain tile polishing waste residue, and waste glass powder to form ceramic blanks, and setting an isolation layer between adjacent ceramic blanks. The resulting ultra-thin recycled ceramic brick is produced through layering, high-temperature firing, and separation, thereby improving the utilization rate of solid waste and reducing firing deformation. CN110746177A discloses a solid waste ceramic brick and its preparation method. This method involves crushing construction waste, ceramic waste, lepidolite roasting and leaching residue, shale, and coal gangue, mixing them with water, aging the mixture, and then extruding and sintering it to obtain solid waste ceramic bricks. This method improves the utilization rate of construction waste and ceramic waste and enhances the strength and apparent density of the ceramic bricks. CN111792914A discloses a method for preparing stoneware antique bricks from multi-source ceramic solid waste. This method involves mixing glaze slag, waste cement, red sand, stone powder, and black mud in a specific ratio, followed by molding and a single firing to produce antique bricks. This achieves the recycling of multi-source ceramic solid waste and reduces production costs. The solutions reported in the above patent literature mainly employ direct mixing of solid waste powders, multi-layer stacking of green bodies, or overall formula adjustment to prepare building ceramic materials. However, these methods cannot simultaneously solve the problems of insufficient stability of the recycled particle coating layer, mismatch between the particle core and the ceramic matrix during firing, and the propagation of interfacial microcracks. In actual production and use, this easily leads to green body warping, increased interfacial porosity, decreased impact resistance, and post-thermal shock strength degradation. Therefore, developing a building ceramic material and its preparation method that combines lightweight, high strength, good thermal shock stability, and high solid waste utilization rate is a pressing technical problem that needs to be solved. Summary of the Invention

[0005] In view of the above-mentioned defects in the prior art, the technical problem to be solved by the present invention is that when preparing lightweight building ceramic materials from recycled solid waste, the structural stability of the coating layer of the coated reinforcing particles in the water-containing slurry is insufficient, the firing shrinkage between the particle core, the coating layer and the ceramic matrix is ​​mismatched, resulting in more interfacial pores and microcracks, as well as insufficient fracture modulus, impact resistance and thermal shock stability of the resulting lightweight ceramic materials. The present invention provides a high-strength lightweight building ceramic material and its preparation method.

[0006] A method for preparing a high-strength, lightweight, and thin building ceramic material includes the following steps:

[0007] Step 1: The waste concrete is sorted to remove steel bars, wood, plastic and gypsum debris. After crushing, magnetic separation and drying, the portion with a particle size of 75-180μm is screened as waste concrete particles. The remaining part is further ground to obtain waste concrete powder with a median particle size D50 of 15-30μm and D90 of no more than 60μm.

[0008] After removing impurities, crushing and drying waste ceramic bricks, the portion with a particle size of 75-180μm is screened out as waste ceramic particles, and the remaining portion is further ground to obtain waste ceramic powder with a median particle size D50 of 20-35μm and D90 of no more than 60μm.

[0009] Waste glass is washed, dried, crushed, and ground to obtain waste glass powder with a median particle size D50 of 5-12 μm and D90 of no more than 25 μm.

[0010] Step 2: Mix waste ceramic particles and waste concrete particles to obtain particle cores; add waste glass powder, metakaolin, wollastonite and sodium silicate to water and stir to obtain basic coating slurry; place the particle cores in a disc granulator and roll them while spraying in the basic coating slurry. After continued rolling, drying and sieving, coated reinforced particles are obtained.

[0011] Step 3: Mix waste ceramic powder, waste concrete powder, waste glass powder, kaolin, potassium feldspar, wollastonite, calcined bauxite and talc, add sodium polyacrylate and sodium carboxymethyl cellulose, and wet ball mill to obtain matrix slurry;

[0012] Step 4: Add the coated reinforcing particles to the matrix slurry and stir to mix. No ball milling is performed during the mixing process. Spray dry the mixed slurry to granulate. The resulting powder is then sieved and sealed for aging to obtain the molded powder.

[0013] Step 5: Load the molding powder into the mold and press it to obtain a ceramic green body; dry the ceramic green body in sequence, remove the binder and sinter it at high temperature, and cool it to room temperature after sintering to obtain a high-strength, lightweight building ceramic material.

[0014] Preferably, in step 2, the mass ratio of the waste ceramic particles to the waste concrete particles is 60:40-80:20, and more preferably 65:35-75:25;

[0015] Preferably, by weight, the basic coating slurry comprises 48-55 parts waste glass powder, 20-24 parts metakaolin, 18-22 parts wollastonite, and 2-4 parts sodium silicate.

[0016] In step 2, while the basic coating slurry is being stirred, a composite interface modification component is added, and stirring is continued while adjusting the solid content to obtain a modified coating slurry. The particle core is placed in a disc granulator and rolled while the modified coating slurry is sprayed in. After continued rolling, drying, and sieving, modified coated reinforced particles are obtained.

[0017] Preferably, the composite interface modification component is at least one of boehmite nanofiber dispersion, zirconium ammonium carbonate solution, and yttrium sol;

[0018] Preferably, the boehmite nanofiber dispersion has a solid content of 8-12%, the zirconium ammonium carbonate solution has a mass concentration of 15-25% based on ZrO2, and the yttrium sol has a solid content of 8-12% based on Y2O3.

[0019] Preferably, the amount of boehmite nanofibers added is 2-6% of the total mass of inorganic powder in the base coating slurry, and the amount of ammonium zirconium carbonate added, calculated as ZrO2, is 0.2-0.6% of the total mass of inorganic powder in the base coating slurry. When the composite interface modification component contains both ammonium zirconium carbonate solution and yttrium sol, the amount of yttrium sol added is determined according to the principle of equal absolute mass of Y2O3, so that the amount added, calculated as Y2O3, is the same as the amount added, calculated as Y2O3, of the yttrium component in the corresponding zirconium-containing scheme.

[0020] Preferably, under the condition of stirring the base coating slurry at 400-600 r / min, a three-way metering pump is used to simultaneously add boehmite nanofiber dispersion, zirconium ammonium carbonate solution and yttrium sol to the base coating slurry. The addition time of the three materials is 6-10 min, and the addition of the three materials is controlled to start and end synchronously.

[0021] Preferably, during the addition of the composite interface modifier, the pH value of the coating slurry is maintained at 9.2-10; before adding the composite interface modifier, the initial water addition of the base coating slurry is controlled according to the amount of composite interface modifier added and its respective solid content, so that the solid content of the coating slurry after all the composite interface modifier is added and before the final solid content adjustment is not lower than the preset final solid content; after the composite interface modifier is added, stirring is continued at 400-600 r / min for 15-25 min, the actual solid content of the resulting coating slurry is measured, and water is added to adjust its solid content to 45-50%.

[0022] Preferably, in step 2, the dry basis mass of the coating layer is 10-16% of the particle core mass, and the particle size of the modified coated reinforcing particles is 80-300 μm.

[0023] Preferably, in step 3, the solid raw materials of the matrix slurry, by mass, include 25-29 parts of waste ceramic powder, 16-20 parts of waste concrete powder, 10-14 parts of waste glass powder, 12-16 parts of kaolin, 8-12 parts of potassium feldspar, 4-8 parts of wollastonite, 4-6 parts of calcined bauxite, and 2-4 parts of talc.

[0024] Preferably, in step 5, the pressing pressure of the ceramic green body is 34-42 MPa, and the holding time is 6-10 s; the dried ceramic green body is heated from room temperature to 280-320℃ at an average heating rate of 6-10℃ / min, then heated to 730-790℃ at 2-4℃ / min and held for 15-25 min, then heated to 1150-1200℃ at 4-6℃ / min and held for 15-22 min; after sintering, it is cooled to room temperature to obtain a high-strength, lightweight building ceramic material with a firing thickness of 4.6-5.3 mm.

[0025] The present invention also provides a high-strength, lightweight building ceramic material prepared by the above-described method.

[0026] Waste ceramic particles and waste concrete particles form a rigid particle core, which can reduce the overall shrinkage of the ceramic matrix during firing. Waste glass powder, metakaolin, wollastonite and sodium silicate form a coating layer on the surface of the particle core, creating a transitional region with gradual compositional changes between the particle core and the ceramic matrix, thus mitigating the difference in firing shrinkage between the two.

[0027] The composite interface modification components include boehmite nanofiber dispersion, zirconium ammonium carbonate solution, and yttrium sol. These three components are simultaneously added to the base coating slurry, allowing zirconium and yttrium species to be simultaneously loaded during the boehmite nanofiber dispersion process, reducing local agglomeration and uneven distribution. The boehmite nanofibers form a fibrous support network through interlocking and utilize surface hydroxyl groups to adsorb zirconium and yttrium species. During the coating drying process, this fiber network can disperse shrinkage stress, reducing coating cracking and detachment. During drying, zirconium ammonium carbonate forms a zirconium-containing inorganic bond structure, improving the bonding strength between the coating and the particle core. During sintering, the boehmite nanofibers transform into an alumina framework, which can limit excessive flow of the glass liquid phase; the zirconium ammonium carbonate transforms into fine zirconium-containing oxides; and the yttrium component can regulate the growth and high-temperature stability of zirconium-containing grains, reducing local stress concentration caused by grain coarsening. This results in a composite transition interface between the particle core and the ceramic matrix, consisting of an alumina framework, yttrium-modified zirconium-containing oxides, and an aluminosilicate glass phase. Composite transition interfaces can improve interface density, reduce annular porosity and microcracks, and gradually transfer external loads from the ceramic matrix to the particle core. When cracks propagate to this interface, the alumina framework and zirconium-containing oxides can deflect, bifurcate, and passivate the cracks, thereby improving the fracture modulus, impact resistance, and thermal shock stability of the ceramic material.

[0028] The beneficial effects of this invention are:

[0029] 1. This invention comprises a composite interface modifier consisting of boehmite nanofiber dispersion, zirconium ammonium carbonate solution, and yttrium sol, which is introduced into the base coating slurry through simultaneous addition. The hydroxyl groups on the surface of the boehmite nanofibers can provide adsorption and loading sites for zirconium and yttrium species, thereby reducing the local agglomeration of zirconium and yttrium components in the coating slurry and improving the uniformity of the distribution of the modifier in the coating layer.

[0030] 2. Boehmite nanofibers, ammonium zirconium carbonate, and yttrium sol work together to form a composite transition interface between the particle core and the ceramic matrix, consisting of an alumina framework, zirconium-containing oxides, and an aluminosilicate glass phase. This interface can buffer the differences in sintering shrinkage and thermal expansion between the particle core, the coating layer, and the ceramic matrix, reduce interfacial porosity and microcracks, and improve the sintering density of the ceramic material.

[0031] 3. The ceramic material prepared by this invention maintains a high utilization rate of waste concrete, waste ceramics and waste glass, while having a high modulus of rupture, impact resistance and post-thermal shock strength retention rate, which can meet the requirements of lightweight, high strength and durability of building ceramic materials. Detailed Implementation

[0032] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0033] Waste concrete originates from production waste, construction waste, or demolition waste of ordinary silicate cement-based building concrete components;

[0034] Waste ceramic bricks originate from production waste, processing waste, or demolition waste of already fired porcelain or stoneware building ceramic bricks;

[0035] Waste glass originates from the production scraps, processing waste, or recycled fragments of soda-lime-silicon glass.

[0036] The yttrium sol used was SS-Y14W type nano-yttrium oxide sol produced by Hangzhou Jikang New Materials Co., Ltd.

[0037] Boehmite nanofibers were prepared by referring to the preparation method in Example 2 of patent CN103553097B.

[0038] The calcined bauxite used is grade 85 calcined bauxite fine powder produced by Gongyi Songfeng Mining Industry Co., Ltd., with an Al2O3 content of not less than 85% and a particle size of 325 mesh.

[0039] Sodium carboxymethyl cellulose was purchased from Changzhou Guoyu Environmental Protection Technology Co., Ltd.

[0040] Sodium polyacrylate was purchased from Shandong Taihe Technology Co., Ltd.

[0041] Other raw materials not mentioned are all common raw materials. The above content is only for the purpose of illustrating the present invention and should not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase the same / similar raw materials from the market or prepare them themselves.

[0042] The technical solutions of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0043] Example 1

[0044] A method for preparing a high-strength, lightweight, and thin building ceramic material includes the following steps:

[0045] Step 1: The waste concrete is sorted to remove steel bars, wood, plastic and gypsum debris. After crushing, magnetic separation and drying, the portion with a particle size of 75-180μm is screened as waste concrete particles. The remaining part is further ground to obtain waste concrete powder with a median particle size D50 of 15-30μm and D90 of no more than 60μm.

[0046] After removing impurities, crushing and drying waste ceramic bricks, the portion with a particle size of 75-180μm is screened out as waste ceramic particles, and the remaining portion is further ground to obtain waste ceramic powder with a median particle size D50 of 20-35μm and D90 of no more than 60μm.

[0047] Waste glass is washed, dried, crushed, and ground to obtain waste glass powder with a median particle size D50 of 5-12 μm and D90 of no more than 25 μm.

[0048] Step 2: Mix the waste ceramic particles and waste concrete particles obtained in Step 1 at a mass ratio of 70:30 to obtain the particle core; add 55 parts of waste glass powder, 22 parts of metakaolin, 20 parts of wollastonite and 3 parts of sodium silicate to water to prepare a coating slurry with a solid content of 48%; place the particle core in a disc granulator and roll it at a speed of 30 r / min while spraying the coating slurry, so that the dry basis mass of the coating layer is 13% of the mass of the particle core. After the slurry is sprayed, continue rolling for 5 min and dry at 110℃ for 2 h. Screen out particles with a particle size of 90-250 μm to obtain coated reinforced particles.

[0049] Step 3: By weight, mix 27 parts waste ceramic powder, 18 parts waste concrete powder, 12 parts waste glass powder, 14 parts kaolin, 10 parts potassium feldspar, 6 parts wollastonite, 5 parts calcined bauxite, and 3 parts talc, and add 0.25% sodium polyacrylate and 0.18% sodium carboxymethyl cellulose by weight of the total raw materials; perform wet ball milling at a mass ratio of dry materials, ball milling stones, and water of 1:2:0.48, at a ball milling speed of 35 r / min, for 8 h, so that the median particle size of the solid particles in the slurry is 8-10 μm, to obtain the matrix slurry;

[0050] Step 4: Based on 95 parts of solid raw materials in the matrix slurry, add 5 parts of coated reinforcing particles and stir at 45 r / min for 15 min. Do not ball mill during the mixing process to maintain the structural integrity of the coated reinforcing particles. Spray dry the mixed slurry to granulate. The inlet temperature of the spray drying tower is 520℃ and the outlet temperature is 85℃. After sieving the powder, seal and age it for 12 h.

[0051] Step 5: Load the aged powder into a mold and press it under 38MPa pressure for 8 seconds to obtain a ceramic green body with a thickness of 5.4mm. Dry the ceramic green body at 80℃ for 30 minutes, and then at 110℃ for 90 minutes. Raise the dried ceramic green body from room temperature to 300℃ at an average heating rate of 8℃ / min. Then raise the temperature to 760℃ at 3℃ / min and hold for 20 minutes. Then raise the temperature to 1175℃ at 5℃ / min and hold for 18 minutes. After sintering, cool to room temperature to obtain a high-strength, lightweight building ceramic material with a firing thickness of 5mm.

[0052] Example 2

[0053] A method for preparing a high-strength, lightweight, and thin building ceramic material includes the following steps:

[0054] Step 1: The waste concrete is sorted to remove steel bars, wood, plastic and gypsum debris. After crushing, magnetic separation and drying, the portion with a particle size of 75-180μm is screened as waste concrete particles. The remaining part is further ground to obtain waste concrete powder with a median particle size D50 of 15-30μm and D90 of no more than 60μm.

[0055] After removing impurities, crushing and drying waste ceramic bricks, the portion with a particle size of 75-180μm is screened out as waste ceramic particles, and the remaining portion is further ground to obtain waste ceramic powder with a median particle size D50 of 20-35μm and D90 of no more than 60μm.

[0056] Waste glass is washed, dried, crushed, and ground to obtain waste glass powder with a median particle size D50 of 5-12 μm and a D90 of no more than 25 μm.

[0057] Step 2: Mix the waste ceramic particles and waste concrete particles obtained in Step 1 at a mass ratio of 70:30 to obtain the particle core; add 55 parts waste glass powder, 22 parts metakaolin, 20 parts wollastonite, and 3 parts sodium silicate to water, and pre-stir at 500 r / min for 10 min, adjusting the initial solid content of the resulting base coating slurry to 60% by controlling the amount of water added; while maintaining the stirring of the base coating slurry at 500 r / min, use a three-way metering pump to dispense the boehmite nanofiber dispersion. (The boehmite nanofiber dispersion has a solid content of 10%), zirconium ammonium carbonate solution (the zirconium ammonium carbonate solution has a mass concentration of 20% based on ZrO2), and yttrium sol (the yttrium sol has a solid content of 10% based on Y2O3) are simultaneously added to the base coating slurry. The addition time for all three materials is 8 minutes, and the addition of the three materials is controlled to start and end simultaneously. Among them, the amount of boehmite nanofiber added is 4% of the total mass of inorganic powder in the base coating slurry, and the amount of zirconium ammonium carbonate added is based on ZrO2. The amount of yttrium sol added is determined according to the following formula: Y₂O₃ accounts for 3% of the total molar amount of Y₂O₃ and ZrO₂ oxides (corresponding to 0.0227% of the total mass of inorganic powder in the basic coating slurry; when using yttrium sol with a solid content of 10% Y₂O₃, the amount of yttrium sol solution added is 0.227% of the total mass of inorganic powder in the basic coating slurry). During the simultaneous addition process, the pH value of the coating slurry is maintained at 9.6. After the material is added, continue stirring at 500 r / min for 20 min, then add water to adjust the solid content of the coating slurry to 48% to obtain the modified coating slurry; place the particle core in a disc granulator and roll it at 30 r / min while spraying the modified coating slurry, so that the dry basis mass of the coating layer is 13% of the particle core mass. After the slurry is sprayed, continue rolling for 5 min and dry at 110℃ for 2 h. Screen out particles with a particle size of 90-250 μm to obtain the modified coated reinforced particles;

[0058] Step 3: By mass, mix 27 parts waste ceramic powder, 18 parts waste concrete powder, 12 parts waste glass powder, 14 parts kaolin, 10 parts potassium feldspar, 6 parts wollastonite, 5 parts calcined bauxite, and 3 parts talc, and add 0.25% sodium polyacrylate and 0.18% sodium carboxymethyl cellulose by mass of the total raw materials; perform wet ball milling at a mass ratio of dry materials, ball milling stones, and water of 1:2:0.48, at a ball milling speed of 35 r / min, for 8 h, so that the median particle size of the solid particles in the slurry is 8-10 μm, to obtain the matrix slurry.

[0059] Step 4: Based on 95 parts of solid raw materials in the matrix slurry, add 5 parts of modified coated reinforcing particles and stir at 45 r / min for 15 min. Do not ball mill during the mixing process to maintain the structural integrity of the coated reinforcing particles. Spray dry the mixed slurry to granulate. The inlet temperature of the spray drying tower is 520℃ and the outlet temperature is 85℃. After sieving the obtained powder, seal and age it for 12 h.

[0060] Step 5: Load the aged powder into a mold and press it under 38MPa pressure for 8 seconds to obtain a ceramic green body with a thickness of 5.4mm. Dry the ceramic green body at 80℃ for 30 minutes, and then at 110℃ for 90 minutes. Raise the dried ceramic green body from room temperature to 300℃ at an average heating rate of 8℃ / min. Then raise the temperature to 760℃ at 3℃ / min and hold for 20 minutes. Then raise the temperature to 1175℃ at 5℃ / min and hold for 18 minutes. After sintering, cool to room temperature to obtain a high-strength, lightweight building ceramic material with a firing thickness of 5mm.

[0061] Example 3

[0062] The process is basically the same as in Example 2, except that in step 2, when preparing the modified coating slurry, only boehmite nanofiber dispersion and zirconium ammonium carbonate solution are added simultaneously, and yttrium sol is not added. The other raw material composition, raw material dosage and process parameters are the same as in Example 2.

[0063] Example 4

[0064] This example is essentially the same as Example 2, except that in step 2, when preparing the modified coating slurry, only boehmite nanofiber dispersion and yttrium sol are added simultaneously; zirconium ammonium carbonate solution is not added. The remaining raw material composition, raw material dosage, and process parameters are the same as in Example 2. Since zirconium ammonium carbonate solution is not added in this example, the proportion of Y₂O₃ to the total molar amount of Y₂O₃ and ZrO₂ oxides is no longer used to determine the amount of yttrium sol added. To control a single variable and maintain the absolute amount of yttrium added the same as in Example 2, the amount of yttrium sol added is determined according to the principle of equal absolute mass of Y₂O₃. When using yttrium sol with a solid content of 10% based on Y₂O₃, the amount of yttrium sol solution added is 0.227% of the total mass of inorganic powder in the base coating slurry, and the corresponding amount of Y₂O₃ added is 0.0227% of the total mass of inorganic powder in the base coating slurry.

[0065] Example 5

[0066] The process is basically the same as in Example 2, except that in step 2, when preparing the modified coating slurry, only zirconium ammonium carbonate solution and yttrium sol are added simultaneously, and boehmite nanofiber dispersion is not added. The other raw material composition, raw material dosage and process parameters are the same as in Example 2.

[0067] Example 6

[0068] The process is basically the same as in Example 2, except that in step 2, when preparing the modified coating slurry, only boehmite nanofiber dispersion is added, and zirconium ammonium carbonate solution and yttrium sol are not added. The composition of other raw materials, the amount of raw materials and the process parameters are the same as in Example 2.

[0069] Example 7

[0070] The process is basically the same as in Example 2, except that in step 2, when preparing the modified coating slurry, only zirconium ammonium carbonate solution is added, and boehmite nanofiber dispersion and yttrium sol are not added. The composition of other raw materials, the amount of raw materials and the process parameters are the same as in Example 2.

[0071] Example 8

[0072] The process is essentially the same as in Example 2, except that in step 2, when preparing the modified coating slurry, only yttrium sol was added, without the boehmite nanofiber dispersion and zirconium carbonate solution. To maintain the same absolute amount of yttrium as in Example 2, the amount of yttrium sol added was determined according to the principle of equal absolute mass of Y₂O₃. When using yttrium sol with a solid content of 10% based on Y₂O₃, the amount of yttrium sol solution added was 0.227% of the total mass of inorganic powder in the basic coating slurry, and the corresponding amount of Y₂O₃ added was 0.0227% of the total mass of inorganic powder in the basic coating slurry; the remaining raw material composition, raw material dosage, and process parameters were the same as in Example 2.

[0073] Test Example 1

[0074] To compare the performance of the high-strength, lightweight building ceramic materials obtained in the examples, three batches of ceramic materials were prepared for each example, and a corresponding number of samples were randomly selected from the three batches for testing. Before testing, the fired ceramic materials were placed in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 24 hours to adjust.

[0075] (1) Interface defect area ratio test:

[0076] Samples with dimensions of 20mm × 20mm were cut from the sintered ceramic materials obtained in each embodiment. The samples were cut along the thickness direction, and after being vacuum impregnated with epoxy resin, ground and polished step by step, a conductive layer was sprayed onto the surface of the samples.

[0077] Scanning electron microscopy was used to observe the interface region between the coated reinforcing particles and the ceramic matrix. A ring-shaped region extending 20 μm inward and outward from the outer boundary of the coated reinforcing particles was selected as the interface statistical region. Five samples were randomly selected from each embodiment, and ten interface fields of view were selected for each sample. Image analysis software was used to identify porosity and microcracks within the interface statistical region.

[0078] The proportion of interface defect area C is calculated according to the following formula:

[0079] C = Area of ​​pores and microcracks in the interface statistical region ÷ Total area of ​​the interface statistical region × 100%.

[0080] The lower the proportion of interface defect area, the better the firing shrinkage matching and interface bonding between the particle core, coating layer and ceramic matrix.

[0081] (2) Water absorption rate test:

[0082] The water absorption rate was tested according to the method specified in GB / T 3810.3. For each embodiment, 10 intact samples were selected, dried to constant weight, and weighed. Then, the samples were boiled to fully absorb water, the surface water was wiped off, and the saturated mass was weighed. The water absorption rate was calculated based on the difference between the saturated mass and the dried mass.

[0083] The lower the water absorption rate, the fewer the open pores inside the ceramic material, and the better the sintering density.

[0084] Table 1. Test results of interface defect area ratio and water absorption rate of high-strength, lightweight building ceramic materials.

[0085] Percentage of interface defect area / % Water absorption rate / % Example 1 4.62±0.31 0.34±0.02 Example 2 0.86±0.12 0.17±0.01 Example 3 1.55±0.18 0.20±0.01 Example 4 2.54±0.22 0.25±0.02 Example 5 2.05±0.2 0.23±0.01 Example 6 2.78±0.24 0.27±0.02 Example 7 3.12±0.26 0.28±0.02 Example 8 4.05±0.29 0.31±0.02

[0086] As shown in Table 1, since no three modified components were added in Example 1, the coating layer lacked a stable inorganic skeleton and interface reinforcement structure. Pores and microcracks were easily formed between the particle core, the coating layer and the ceramic matrix due to the difference in firing shrinkage. Therefore, the proportion of interface defect area and water absorption rate were the highest.

[0087] In Example 6, the addition of boehmite nanofibers alone resulted in the fibers forming an overlapping structure within the coating layer, which transformed into an alumina framework after sintering. This suppressed excessive flow of the glass liquid phase, leading to a decrease in both performance indicators. In Example 7, the addition of ammonium zirconium carbonate alone formed a zirconium-containing inorganic bonded structure, but lacking the dispersing effect of boehmite nanofibers, the zirconium component tended to aggregate locally, resulting in a lower improvement than in Example 6. In Example 8, only a small amount of yttrium sol was added, and there were no zirconium oxide precursors or fiber carriers, primarily exerting a limited grain boundary regulation effect, thus yielding the smallest improvement. In Example 3, boehmite nanofibers provided adsorption and dispersion sites for zirconium species, while ammonium zirconium carbonate enhanced the bonding between the fibers and the coating layer. Together, they formed a composite interface of alumina and zirconium-containing oxides, significantly reducing the interface defect area ratio and water absorption rate. In Example 4, the lack of ammonium zirconium carbonate made it difficult for the yttrium component to form a significant zirconium-containing reinforced structure, resulting in limited improvement. In Example 5, the zirconium ammonium carbonate and yttrium sol can form a relatively stable and fine zirconium-containing structure, but it lacks a boehmite nanofiber framework, and its dispersion uniformity and high-temperature morphology retention are still lower than those of Example 2. Example 2 incorporates three components simultaneously: boehmite nanofibers provide the framework and dispersion carrier, zirconium ammonium carbonate improves the interfacial bonding strength and forms zirconium-containing oxides, and the yttrium component inhibits abnormal growth of zirconium-containing grains. Together, these three components form a uniform and dense composite transition interface; therefore, Example 2 has the lowest proportion of interfacial defect area and water absorption rate.

[0088] Test Example 2

[0089] (1) Fracture modulus test:

[0090] The modulus of fracture was tested according to GB / T 3810.4-2016. For each embodiment, 10 strip specimens with dimensions of 200mm × 50mm were cut from the sintered ceramic material, and the actual width and thickness of each specimen were measured. The specimens were placed on two support rollers of a universal testing machine with a support span of 150mm, and a three-point bending method was used to continuously load the specimen at a loading rate of 1mm / min until the specimen fractured. The maximum fracture load was recorded.

[0091] The modulus of fracture R is calculated according to the following formula:

[0092] R = 3FL ÷ (2bh) 2 ).

[0093] In the formula, F is the maximum breaking load in N; L is the support span in mm; b is the specimen width in mm; h is the specimen thickness in mm; and R is the modulus of rupture in MPa.

[0094] (2) Impact resistance test:

[0095] Impact resistance was tested according to the coefficient of restitution method specified in GB / T 3810.5. The specimen was fixed on a specified support, and a steel ball was dropped freely from a fixed height to impact the central region of the specimen. The motion state of the steel ball before and after the impact was recorded, and the coefficient of restitution was calculated.

[0096] Ten samples were selected for each embodiment, and each sample was tested once. The higher the coefficient of restitution, the stronger the elastic recovery ability of the sample after being impacted, and the better its impact resistance.

[0097] (3) Enhanced thermal shock cycling test:

[0098] The test was conducted according to the basic principles of GB / T 3810.9, and with an increased number of cycles. For each embodiment, 20 strip specimens were selected, with 10 specimens used to test the pre-thermal shock modulus of fracture and the other 10 specimens used for thermal shock cycling.

[0099] The thermal shock sample was placed in a constant temperature chamber at 180±5℃ for 30 min, then quickly transferred to water at 20±2℃ for 5 min to cool, and then placed in room temperature air for 10 min to complete one thermal shock cycle. This process was repeated 20 times.

[0100] After thermal shock cycling, the specimen was dried at 110℃ for 2 hours, cooled to room temperature, and the modulus of rupture after thermal shock was determined according to the rupture modulus test method. The strength retention rate T after thermal shock was calculated according to the following formula:

[0101] T = Average fracture modulus after thermal shock ÷ Average fracture modulus before thermal shock × 100%.

[0102] Table 2 Test results of mechanical properties and thermal shock stability of high-strength, lightweight, and thin building ceramic materials

[0103] Fracture modulus / MPa Impact recovery coefficient Strength retention rate after thermal shock / % Example 1 52.8±2.3 0.72±0.02 73.4±2.7 Example 2 78.6±2.8 0.87±0.01 94.1±1.8 Example 3 69.9±2.6 0.81±0.02 86.5±2.0 Example 4 61.8±2.5 0.77±0.02 80.8±2.3 Example 5 67.4±2.7 0.82±0.02 88.2±2.1 Example 6 60.9±2.4 0.76±0.02 79.6±2.4 Example 7 58.7±2.2 0.77±0.02 78.1±2.5 Example 8 54.6±2.1 0.73±0.02 75.0±2.6

[0104] As shown in Table 2, there are many pores and interfacial microcracks around the reinforcing particles in Example 1. These cracks are prone to initiation and propagation during bending, impact, and thermal cycling. Therefore, the fracture modulus, impact recovery coefficient, and strength retention rate after thermal shock are the lowest.

[0105] In Example 6, the boehmite nanofibers, after sintering, form an alumina framework, which improves interfacial load-bearing capacity and crack resistance, thus significantly enhancing the fracture modulus and thermal shock stability. In Example 7, the zirconium-containing oxide can deflect impact cracks to some extent, but due to the lack of a fiber framework and yttrium stabilization, the overall reinforcing effect is limited. In Example 8, the yttrium component alone is used in small quantities and cannot form a significant load-bearing or toughening structure; therefore, its performance is only slightly higher than that of Example 1.

[0106] In Example 3, the alumina framework and zirconium-containing oxides jointly bear the load and hinder crack propagation, significantly improving all three properties. However, due to the lack of yttrium, the high-temperature stability of the zirconium-containing grains is insufficient. In Example 4, lacking zirconium-containing oxides, the yttrium component can only help improve grain boundary bonding, resulting in a small improvement in performance. In Example 5, the yttrium component can improve the stability of the zirconium-containing structure, thus exhibiting good impact and thermal shock resistance. However, lacking the continuous framework formed by boehmite nanofibers, the fracture modulus is lower than that of Example 3.

[0107] In Example 2, the alumina framework formed by boehmite nanofibers is responsible for bearing and transmitting stress, the zirconium-containing oxide formed by ammonium zirconium carbonate deflects and passivates cracks, and the yttrium component further stabilizes the zirconium-containing grains. The three components synergistically improve the interface density and stress dispersion ability, thus Example 2 has the highest fracture modulus, impact recovery coefficient, and post-thermal shock strength retention rate.

[0108] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.

Claims

1. A method for preparing a high-strength, lightweight, and thin building ceramic material, characterized in that, Includes the following steps: Step 1: After sorting, crushing, magnetic separation and drying, waste concrete is screened to obtain waste concrete particles, and the rest is ground to obtain waste concrete powder; after removing impurities, crushing and drying waste ceramic bricks, a portion is screened to obtain waste ceramic particles, and the rest is ground to obtain waste ceramic powder; waste glass is washed, dried, crushed and ground to obtain waste glass powder. Step 2: Mix the waste ceramic particles and waste concrete particles to obtain particle cores; add waste glass powder, metakaolin, wollastonite and sodium silicate to water and stir to obtain basic coating slurry; place the particle cores in a disc granulator and roll them while spraying the basic coating slurry in; after continued rolling, drying and sieving, coated reinforced particles are obtained. Step 3: Mix waste ceramic powder, waste concrete powder, waste glass powder, kaolin, potassium feldspar, wollastonite, calcined bauxite and talc, add sodium polyacrylate and sodium carboxymethyl cellulose, and wet ball mill to obtain matrix slurry; Step 4: Add the coated reinforcing particles to the matrix slurry and stir to mix. No ball milling is performed during the mixing process. Spray dry the resulting slurry to granulate it. The resulting powder is then sieved and sealed for aging to obtain the molded powder. Step 5: The molding powder is loaded into a mold and pressed to obtain a ceramic green body; the ceramic green body is dried and sintered in sequence, and after cooling, the high-strength, lightweight building ceramic material is obtained.

2. The method for preparing high-strength, lightweight, and thin building ceramic materials as described in claim 1, characterized in that: In step 2, while the basic coating slurry is being stirred, a composite interface modification component is added, and stirring is continued while adjusting the solid content to obtain a modified coating slurry. The particle core is placed in a disc granulator and rolled while the modified coating slurry is sprayed in. After continued rolling, drying, and sieving, modified coated reinforced particles are obtained.

3. The method for preparing high-strength, lightweight, and thin building ceramic materials as described in claim 2, characterized in that: The composite interface modification component is at least one of boehmite nanofiber dispersion, zirconium ammonium carbonate solution, and yttrium sol.

4. The method for preparing high-strength, lightweight, and thin building ceramic materials as described in claim 1, characterized in that: In step 1, the particle sizes of the waste concrete particles and waste ceramic particles are 75-180 μm, respectively; The median particle size D50 of the waste concrete powder is 15-30 μm and D90 is no greater than 60 μm; the median particle size D50 of the waste ceramic powder is 20-35 μm and D90 is no greater than 60 μm; and the median particle size D50 of the waste glass powder is 5-12 μm and D90 is no greater than 25 μm.

5. The method for preparing high-strength, lightweight, and thin building ceramic materials as described in claim 1, characterized in that: In step 2, the mass ratio of the waste ceramic particles to the waste concrete particles is 60:40-80:

20.

6. The method for preparing high-strength, lightweight, and thin building ceramic materials as described in claim 1, characterized in that: By weight, the basic coating slurry comprises 48-55 parts waste glass powder, 20-24 parts metakaolin, 18-22 parts wollastonite, and 2-4 parts sodium silicate.

7. The method for preparing high-strength, lightweight, and thin building ceramic materials as described in claim 1, characterized in that: In step 5, the pressing pressure of the ceramic green body is 34-42 MPa, and the holding time is 6-10 s; The ceramic green body is first dried at 70-90℃ for 20-40 min, and then dried at 100-120℃ for 60-120 min. The dried ceramic green body is then heated from room temperature to 280-320℃ at an average heating rate of 6-10℃ / min, then heated to 730-790℃ at 2-4℃ / min and held for 15-25 min, and then heated to 1150-1200℃ at 4-6℃ / min and held for 15-22 min. After sintering, it is cooled to room temperature to obtain a high-strength, lightweight building ceramic material with a firing thickness of 4.6-5.3 mm.

8. The method for preparing high-strength, lightweight, and thin building ceramic materials as described in claim 2 or 3, characterized in that: In step 2, the dry basis mass of the coating layer is 10-16% of the mass of the particle core; The core of the particle is rolled at a speed of 25-35 r / min in a disc granulator. After the modified coating slurry is sprayed in, it continues to roll for 3-8 min and is dried at 100-120℃ for 1-3 h. Modified coated reinforced particles with a particle size of 80-300 μm are obtained by sieving.

9. The method for preparing high-strength, lightweight, and thin building ceramic materials as described in claim 1, characterized in that: In step 3, the solid raw materials of the matrix slurry, by mass, include 25-29 parts of waste ceramic powder, 16-20 parts of waste concrete powder, 10-14 parts of waste glass powder, 12-16 parts of kaolin, 8-12 parts of potassium feldspar, 4-8 parts of wollastonite, 4-6 parts of calcined bauxite, and 2-4 parts of talc. The amount of sodium polyacrylate added is 0.2-0.3% of the total mass of the solid raw materials, and the amount of sodium carboxymethyl cellulose added is 0.14-0.22% of the total mass of the solid raw materials. Wet ball milling was performed with dry material, ball stones and water in a mass ratio of 1:1.8-2.2:0.44-0.52 to make the median particle size of the solid particles in the matrix slurry 7-11 μm.

10. A high-strength, lightweight, and thin building ceramic material, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of nano-fiber boehmite material

    CN103553097B

  • Ultra-thin renewable ceramic brick and making method thereof

    CN104326734A

  • Solid waste ceramic tile and preparation method thereof

    CN110746177A

  • Method for preparing stoneware archaized brick from multi-source ceramic solid wastes

    CN111792914A